Transit Time Distributions and Apparent Oxygen Utilization Rates in Northern South China Sea Using Chlorofluorocarbons and Sulfur Hexafluoride Data. Issue 8 (26th July 2021) - Wang, Weimin; Cai, Minggang; Huang, Peng; Ke, Hongwei; Liu, Mian; Liu, Lihua; Deng, Hengxiang; Luo, Bojun; Wang, Chunhui; Zheng, Xuehong; Li, Wenquan
Abstract: CFC‐12 and SF6 data were used in combination to estimate the mean age of water in the northern South China Sea (NSCS), to explore oceanographic processes related to "time, " including the transit time through the Luzon Strait (LS) with a three‐layer circulation structure and the apparent oxygen utilization rates (AOUR). Significant differences in mean ages of water were observed at the same density level in the water columns on both sides of the LS, presented as a westward flow in the upper layer, eastward flow in the intermediate layer, and westward flow in the deep layer with transit times of 8 ± 5, 39 ± 22, and 20 ± 18 yr, respectively. The AOUR was estimated to be 8.4 μmol kg −1  yr −1 at about 100 m and decreased to approximately 0.66 μmol kg −1  yr −1 at 1, 500 m in the NSCS. The average organic carbon flux in the depth range of 100–1, 500 m was 1.7 mol C m −2  yr −1 in the NSCS and 1.3 mol C m −2  yr −1 in the western Pacific Ocean (WP). The activation energy—derived using the Arrhenius equation—in the NSCS and WP (87.7–154.2 kJ mol −1 ) are close to those in the northern Pacific Ocean (60.8–133.5 kJ mol −1 ). These results suggest a conspicuous correlation between temperature and AOUR. The impact of climate change on the ocean and the feedback mechanism between ocean warming and oxygen consumption needs further investigation. Plain Language Summary: CFC‐12 and SF6 are industrial gases with a changing ratio in the atmosphere that can be used to estimate the age of water masses since their last atmospheric contact. Here CFC‐12 and SF6 data were combined to estimate the water ages in the South China Sea (SCS). The transit times of flow through the Luzon Strait (LS) were assessed and found to be shorter in the upper and deep layers than the intermediate layer. The apparent oxygen utilization rate (AOUR), calculated from oxygen deficiency and water age, reflects oxygen consumption primarily due to microbial respiration. Oxygen consumption rates in the ocean have for over 50 yr been reported as a function of depth with no theoretical basis. Recent work has shown that the tracer derived respiration rates follow classical temperature based thermodynamic theory. Here, we extend this observation to estimate the AOUR in the SCS and the LS and verify the critical role of temperature on biogeochemical rates. Our results imply that ocean warming will have a significant effect on declining ocean oxygen levels and increase the trend toward hypoxia. Key Points: CFC‐12 and SF6 are combined to constrain transit timescales, providing oceanographic rate information Transit times across the Luzon Strait were assessed and found to be shorter in the upper and deeper layers than in the intermediate layer Activation energy corresponding to the oxygen consumption was estimated from the correlation between temperature and biogeochemical rates